A novel material Cs2RbxAg1−xIn0.875Bi0.125Cl6 with a special blue shift and application for white light LED devices. Issue 41 (17th October 2022) - Wang, Xixiang; Niu, Chen; Liao, Wenjian; Mei, Shiliang; Hu, Rongrong; Li, Yang; Yang, Bobo; Chen, Yong; Zou, Jun
Abstract : A lead-free perovskite of Cs2 Rb x Ag1− x In0.875 Bi0.125 Cl6 was synthesized by a hydrothermal method. Properties were characterized in detail and a LED device package was developed with desirable performance promising for lighting applications. Abstract : Perovskite microcrystals have attracted wide attention and have been applied in extensive optical applications. The CsPbX3 perovskite poses a great threat to the environment due to the presence of lead (Pb), and there is an urgent need to improve the photoluminescence quantum yield. Therefore, a lead-free perovskite microcrystal material Cs2 Rb x Ag1− x In0.875 Bi0.125 Cl6 with a high photoluminescence quantum yield (PLQY) was synthesized by a convenient hydrothermal method, with comprehensive characterization of both the structure and optical performance at varying Rb ratios. Optimal properties were observed at x = 0.15 with bright white emission and a PLQY of 32.15%. Superior stability of the novel material in ethanol was observed under the radiation of an excitation light of 365 nm. Interestingly, a blue shift of the emission peak occurred after exposure to humid air, possibly due to the reconstruction of the crystal structure. Moreover, a LED device packaged with this novel material was developed with a desirable color temperature of 3190 K, promising for further lighting applications.